2006
DOI: 10.1167/6.10.9
|View full text |Cite
|
Sign up to set email alerts
|

Induced visual fading of complex images

Abstract: Visual stimuli fade from awareness under retinal stabilization or careful fixation, a phenomenon documented by Troxler more than 200 years ago. Research on visual fading during normal visual fixation typically has been restricted to discrete, simple, low-contrast shapes presented peripherally against a uniform or textured background. In four experiments, we document a striking new visual fading effect in which entire photographs of scenes fade to a uniform luminance and hue during normal visual fixation. Criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…However, MIB is also a “visual disappearance” or fading phenomena, in which otherwise salient visible stimuli disappear from awareness, as if erased in front of the observer's eyes. These include binocular rivalry [2], “generalized flash suppression” [3], artificial scotoma [4], Troxler fading [5] and the related “scene fading” effect [6]. The interest in MIB and the other disappearance effects stems from the all-or-none nature of the illusory disappearance, which could be useful for identifying the neural correlates of consciousness [7] and the intrinsic mechanisms underlying perceptual organization [2], [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, MIB is also a “visual disappearance” or fading phenomena, in which otherwise salient visible stimuli disappear from awareness, as if erased in front of the observer's eyes. These include binocular rivalry [2], “generalized flash suppression” [3], artificial scotoma [4], Troxler fading [5] and the related “scene fading” effect [6]. The interest in MIB and the other disappearance effects stems from the all-or-none nature of the illusory disappearance, which could be useful for identifying the neural correlates of consciousness [7] and the intrinsic mechanisms underlying perceptual organization [2], [8].…”
Section: Introductionmentioning
confidence: 99%
“…For example in Troxler fading, prolonged fixation causes stimuli in the periphery (Troxler, 1804), or, as has been shown more recently, even entire scenes (Simons et al, 2006) to disappear from view. As adaptation causes luminance boundaries to break down, color may spread beyond that boundary.…”
Section: Discussionmentioning
confidence: 98%
“…1C). Numerous authors have reported the fading of foveal targets previously (Darwin, 1795;Troxler, 1804;Krauskopf, 1963;Pessoa and De Weerd, 2003;Simons et al, 2006), including Troxler himself: "Troxler's effect has become associated almost exclusively with the disappearances of peripheral targets, but it is noteworthy that Troxler himself reported that the central fixation target disappeared after prolonged observation" (Wade and Tatler, 2005). No study to date has determined the impact of microsaccades on counteracting foveal fading, however.…”
Section: Discussionmentioning
confidence: 99%